2021
DOI: 10.1093/g3journal/jkab334
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in nonlinear responses to soil moisture shapes evolutionary constraints in Brachypodium

Abstract: Water availability is perhaps the greatest environmental determinant of plant yield and fitness. However, our understanding of plant-water relations is limited because—like many studies of organism-environment interaction—it is primarily informed by experiments considering performance at two discrete levels—wet and dry—rather than as a continuously varying environmental gradient. Here we used experimental and statistical methods based on function-valued traits to explore genetic variation in responses to a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
2
6
0
Order By: Relevance
“…The degree of stress imposed on the system may dictate whether coherence (or integration) as opposed to decoherence is observed. A possible reconciliation between our results and the decoherence reported by Lea et al, may be that the monocytes studied by Lea et al experienced a relatively more stressful environment than the rice plants studied by Wilkins et al Indeed, we recently showed that trait co-variances vary considerably along a single environmental index (Monroe et al 2021), suggesting that genome-scale regulatory interactions likely transition from coherent to decoherent along such axes. Such gradients of response should be carefully considered during the design of experiments (Poorter et al 2016).…”
Section: Discussionsupporting
confidence: 75%
“…The degree of stress imposed on the system may dictate whether coherence (or integration) as opposed to decoherence is observed. A possible reconciliation between our results and the decoherence reported by Lea et al, may be that the monocytes studied by Lea et al experienced a relatively more stressful environment than the rice plants studied by Wilkins et al Indeed, we recently showed that trait co-variances vary considerably along a single environmental index (Monroe et al 2021), suggesting that genome-scale regulatory interactions likely transition from coherent to decoherent along such axes. Such gradients of response should be carefully considered during the design of experiments (Poorter et al 2016).…”
Section: Discussionsupporting
confidence: 75%
“…Although the literature describing drought responses in plants is extensive, Brachypodium-based research has made a contribution. At its most basic, an examination of Brachypodium inbred lines grown under range of soil % moisture contents indicated a nonlinear relationship, so simple pairwise comparisons between droughted and fully watered plants could be insufficient [75]. The variation in responses to drought in Brachypodium accessions has been assessed [34,76,77] and, in one case, the degree of drought tolerance related to rainfall in the original sampling sites [78].…”
Section: Brachypodium To Elucidate Plant Responses To Environmental S...mentioning
confidence: 99%
“…This observation may be related to exponential decreases in soil water potential at low SWCg ( Dowd et al 2019 ), whereby a small change in water volume leads to a large change in water availability. Moreover, physiological and growth traits, including specific leaf area and leaf carbon content, are affected non-linearly by soil water availability ( Monroe et al 2021 ) highlighting the importance of studying these responses under a limited number of discrete soil moisture conditions. To fully characterize plant responses to drought stress, it will be necessary to incorporate intermediate water-limiting conditions to understand how the degree of water stress impacts plant status, rather than an ‘all-or-nothing’ approach.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments that have directly compared drought-stress responses in controlled and field environments have reported significant differences in physiological responses and gene expression profiles depending on the type of environments where plants were grown ( Lovell et al 2016 ; Wilkins et al 2016 ). Some of these differences can be attributed to the degree or duration of the drought ( Monroe et al 2021 ), or to the underlying complexity of the environment ( Mittler 2006 ; Plessis et al 2015 ). In nature, the onset of drought is often gradual, and plants adjust their physiology and development to minimize damage and optimize growth ( Sohn et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%